Discussions on locally-led humanitarian assistance amongst European INGOs and donors — shifting practices or challenging mental models? - Sever Dzigurski; Cindy Horst (Fennia: International Journal of Geography)
This reflection piece explores the mental models underlying the formalized humanitarian system and the localization debates within it. The authors argue that these mental models draw on neoliberal and Eurocentric development logic that have been challenged in post-capitalist, post-development and post-postcolonial theory. A demand for more radical transformation of the system would entail acknowledging other mental models that de-center the global north while at the same time creating space for conversations about power that recognize historically grounded, structural power inequalities. These alternative perspectives are grounded in a relational ethics that emphasizes interconnectedness and interdependence, is rooted in reciprocity, solidarity, and care, and values long-term relationships shaped by shared histories and collective futures. While at present, discussions on locally-led approaches often separate the realm of mental models and practical operationalisations, we argue that there are elements that connect the two — with mental models impacting ideas about technical solutions and vice versa.